Discovery of molecular-line polarization in the disk of TW Hya - Teague, Richard; Hull, Charles L. H.; Guilloteau, Stéphane; Bergin, Edwin A.; Dutrey, Anne; Henning, Thomas; Kuiper, Rolf; Semenov, Dmitry; Stephens, Ian W.; Vlemmings, Wouter H. T. (The astrophysical journal, 2021)
We report observations of polarized line and continuum emission from the disk of TW Hya using the Atacama Large Millimeter/submillimeter Array. We target three emission lines, 12CO (3-2), 13CO (3-2), and CS (7-6), to search for linear polarization due to the Goldreich-Kylafis effect, while simultaneously tracing the continuum polarization morphology at 332 GHz (900 μm), achieving a spatial resolution of 0.″5 (30 au). We detect linear polarization in the dust continuum emission; the polarization position angles show an azimuthal morphology, and the median polarization fraction is ∼0.2%, comparable to previous, lower frequency observations. Adopting a “shift-and-stack” technique to boost the sensitivity of the data, combined with a linear combination of the Q and U components to account for their azimuthal dependence, we detect weak linear polarization of 12CO and 13CO line emission at a ∼10σ and ∼5σ significance, respectively. The polarization was detected in the line wings, reaching a peak polarization fraction of ∼5% and ∼3% for the two molecules between disk radii of 0.″5 and 1″. The sign of the polarization was found to flip from the blueshifted side of the emission to the redshifted side, suggesting a complex, asymmetric polarization morphology. Polarization is not robustly detected for the CS emission; however, a tentative signal, comparable in morphology to that found for the 12CO and 13CO emission, is found at a ≲3σ significance. We are able to reconstruct a polarization morphology, consistent with the azimuthally averaged profiles, under the assumption that this is also azimuthally symmetric, which can be compared with future higher-sensitivity observations.
Gesehen am 27.01.2022